Implementation of The Sorogan Baca Program to Strengthen Early Childhood Pre-Reading Ability - Fitriah, Nurlaeli; Anisah, Mupi; Khasanah, Rahma Laylatul; Merzhindi, Charvienli Pudji (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the application of the sorogan baca method in improving pre-reading skills among early childhood learners at TK Muslimat NU 1 Sukolilo. Using a qualitative approach, data were collected through observation, interviews, and documentation. This study involved teachers and students as its main subjects. The findings of the study indicate that the sorogan baca program improved children's pre-reading skills, providing them with a strong foundation for the transition to elementary school. Program improvement was observed in areas such as phonological awareness, letter recognition, and the ability to blend letters into meaningful words. The aspect of phonological awareness is seen in children, for example when they are asked to read or pronounce vowels with a loud and clear voice. The aspect of letter recognition is shown in this sorogan baca activity when the teacher pronounces certain letters, then the students will point to which shape/letter is meant. And the ability to combine letters into meaningful words can be seen through the child's ability to match all sounds with the right letters, know the letters in the word, and understand the word. In addition, this program provides an alternative model for strengthening early literacy by adopting a pesantren cultural approach that is very close to the community. However, it does not ignore the concept of playing in early childhood learning. This fosters an interesting learning environment and encourages active participation of children..